Qualidade do ciberjornalismo profissional e amador: estudo comparativo - Zamith, Fernando (2015)
In recent decades of online media, numerous questions have been placed especially to the direction that journalism has followed, with a serious risk of quality loss and consequent adverse effects on society and democracy. Among these questions, we can highlight: - Entry to the online journalism process of people (the former audience, citizen journalists) unprepared and unaware of ethical procedures; - Loss of control by journalists from many of the processes of dissemination and appropriation of news, now shared, commented, amputated and retold in social media; - Increasing tendency to automation use, throughout feeds, aggregation, and robots-journalists (Marshall, 2013), sometimes without the necessary prior control by human editors / reporters, and endangering the quality of journalism. - Multi-task online journalists, with no time or experience to do quality journalism, "comprehensive and proportional" (Kovach & Rosenstiel, 2001); - Strong priority given to immediacy by online news media, in prejudice of an in-depth and contextualized online journalism. The questions listed above are clearly new questions brought by the Internet and by the recent technologic advances, and in some cases have increased not-resolved problems concerning quality journalism in traditional media. That's why we believe that we need to find a tool specifically to measure the quality of online news. The main goal of this paper is to present the results of a preliminary research using the "5 C's and 1 A" framework: comprehensibility, context, causality, comparativeness, comprehensiveness and accuracy (Anderson, 2014: 21-23) to evaluate the quality of online news and its producers. The sample was nine news articles from different authors (professional and amateur) selected and voted by users of the Digg aggregator. Unsurprisingly, we conclude that the professional online journalism notes better quality levels. We conclude also that the "former audience" (Gillmor, 2004; Rosen, 2006) seems to prefer long news articles of investigative journalism ("slow journalism") and not the "fast journalism" of immediate 140 characters.